A unified thermal vibration and transient analysis for quasi-3D shear deformation composite laminated beams with general boundary conditions. (15th May 2021) - Shao, Dong; Wang, Qingshan; Tao, Yongqiang; Shao, Wen; Wu, Wei
Highlights: A unified model is established for solving the thermal vibration and transient behavior of laminated beams firstly. A general quasi-3D hybrid type HSDT for the thermal vibration and transient analysis is proposed. The present moedel is use to handle laminated beams with many kinds of boundary conditions. The quasi-3D HSDT based MRRM is an accurate and effective numerical method. Parametric studies for thermal vibration and transient behavior of laminated beams with different geometrical and material parameters are carried out. Abstract: A unified procedure is proposed in this study to analyze the free and transient vibration behaviors of a composite laminated beam subjected to general boundary conditions under thermal scenario. A general theoretical quasi-3D shear deformation beam model incorporating both the shear deformation and thickness stretching effects is derived using the Hamilton's principle. The coupling of axial–shear–flexural–stretching with the thermal stress and the Poisson's ratio effect is taken into account. The natural frequencies, mode shapes and transient responses of composite laminated beams are evaluated analytically by the method of reverberation ray matrix (MRRM). The inhomogeneous term and the artificial spring boundary technique are introduced in MRRM to acclimatize itself to the general boundary conditions and the impulse loads of arbitrary distributions. The validity, reliability and efficiency of the proposed analytical solutions are verified by comparing with the results obtained from the published studies and finite element simulation. A considerable number of parametrical studies for the composite laminated beams with different elastic restraint parameters, lamination schemes, geometry parameters, material properties as well as various temperature rises are also analyzed and discussed. The present procedure is powerful in terms of its applicability for different high-order shape functions including polynomial and non-polynomial, as well as thin and thick beams subjected to arbitrary boundary conditions in practical engineering. Graphical abstract: Image, graphical abstract